2021
DOI: 10.35484/pssr.2021(5-i)23
|View full text |Cite
|
Sign up to set email alerts
|

US Media’s Agenda-Setting: Analysis of Editorial Presentations of Pakistan

Abstract: The present research aims to identify the agenda items that are used by US newspapers in Pakistan. Fifteen agenda items were selected through an extensive review of literature. To delimit the population only editorials, having the word Pakistan in the initial sentences were selected for analysis. Every sentence of the editorial was taken as the unit of analysis. Quantitative content analysis of the editorials was conducted for identification of agendas and their relation to different propaganda items. It was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Hence, the press of these nations also glorifies the military leadership of their armed forces to create a favorable public image of their armed forces. In a study conducted by Manzoor et al (2021) on the patterns of print media agendas in the context of war-onterror in Pakistan, it was concluded that "terrorism" was an extensively used word in two leading US newspapers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the press of these nations also glorifies the military leadership of their armed forces to create a favorable public image of their armed forces. In a study conducted by Manzoor et al (2021) on the patterns of print media agendas in the context of war-onterror in Pakistan, it was concluded that "terrorism" was an extensively used word in two leading US newspapers.…”
Section: Resultsmentioning
confidence: 99%
“…Later on, the Bush administration used US media extensively to project the military achievements in the Middle East (Le, 2016). In a study conducted by Manzoor et al (2021) on the patterns of print media agendas in the context of war-on-terror in Pakistan, and it was concluded that "terrorism" was an extensively used word in two leading US newspapers.…”
Section: Agenda-setting Of Media and Public Perceptionmentioning
confidence: 99%